Comparative genomic analysis of two putative novel Idiomarina species from hypersaline miocene deposits - Soňa Brestovičová; Jana Kisková; Lea Nosáľová; Mária Piknová; Mariana Kolesárová; Peter Pristaš (BMC Genomics)
Abstract Background Hypersaline habitats, as extreme environments, are a great source of well-adapted organisms with unique properties as they have evolved various strategies to cope with these extreme conditions. Bioinformatics and genomic mining may shed light on evolutionary relationships among them. Therefore, the aim of this study was to assess the biodiversity and especially the strategies evolved within the Idiomarina genus, with the primary focus on the taxonomy and genomic adaptations of two novel strains affiliated with Idiomarina genus isolated from unique environment – brines of two Early Miocene salt deposits. Results Both analyzed species belonged to the Idiomarina loihiensis cluster with similarity levels of 16S rRNA gene sequences as high as 99.5% and showed a significant genome size reduction, known characteristic of Idiomarina genomes, though within the genome of Sol25 strain the lowest extent of the carbohydrate utilization genes reduction was observed t among the Idiomarina species. Moreover, the comparative genome analyses indicated that despite both strains being isolated from geographically and geologically similar environments (brines from at least 12 Ma), the species showed higher relatedness to other Idiomarina species than to each other. Conclusion The present findings highlighted the importance of genomic data in resolving taxonomic uncertainties and understanding of adaptation strategies of extremophiles. Geographic isolation likely contributed to population divergence of the Idiomarina genus, and the recent study offered insights into biogeographic patterns and allopatric speciation of this bacterial group.